Bridging the Gap: Assessing Computer Literacy Among First-Year ITE Students - Yumen, Nolan (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2024)
This study assessed the awareness of basic computer concepts and terminology among 461 first-year students enrolled in Information Technology Education (ITE) programs at the University of Antique Tario-Lim Memorial Campus during the first semester of Academic Year 2024-2025. A descriptive quantitative research design was employed, utilizing a structured survey questionnaire to evaluate students' familiarity with fundamental computer concepts across Bachelor of Science in Information Technology (BSIT), Computer Science (BSCS), and Information Systems (BSIS) programs. Results revealed moderate familiarity with basic concepts but significant gaps in advanced areas such as programming languages, cybersecurity, and software development life cycle. BSCS students demonstrated stronger familiarity with hardware and software applications, while BSIS students excelled in information systems. The study identified a pressing need for targeted educational interventions, particularly for students from non-ICT backgrounds. These findings underscore the importance of aligning curriculum development with students' diverse preparatory needs and industry expectations. The research contributes valuable insights for enhancing IT education strategies and suggests the implementation of remedial courses to bridge knowledge gaps, thereby improving students' academic and professional prospects in the rapidly evolving IT field.